Jonge ouderen: last of lust? Kathrin Komp. The young old in Europe – Burden on or resource to the welfare state? - Polder, Johan J.; Komp, Kathrin (Tijdschrift voor Gerontologie en Geriatrie, 2011)
bespreking proefschriftKathrin Komp. The young old in Europe – Burden on or resource to the welfare state?